Indonesia’s National Strategic Project, Displacement, and the New Poverty - Sekar Banjaran Aji; Achmad Firas Khudi (Journal of Southeast Asian Human Rights, 2021)
The Government of Indonesia initiated the National Strategic Project comprising a wide range of infrastructure programs across the nation in 2016. The project is indicated by a set of supporting regulations and funding schemes. One of the project's supporting laws is Presidential Decree No. 56/2017 on the mitigation of land procurement social impact. This study seeks to examine the impacts of Indonesia's national strategic project, focusing on socio-economic deprivations and suggesting relevant policy frameworks for the displaced population regarding their well-being and human rights. The desk review of displacement status and human rights will provide an analysis of displacement people's socio-economic condition and fundamental rights of displaced people from a selected district in which displacement has been occurring since 2016. The case study of the chosen community will elucidate the causes and consequences of this displacement case. We will utilize both qualitative and quantitative data taken from official government reports and affected residents.